Bladder Endometriosis that Invisible to Repeated Cystoscopies: A Case Report - Ida Bagus Putra Adnyana (Journal of Global Pharma Technology, 2019)
Background: Bladder endometriosis (BE) is a form of Deep Infiltrating Endometriosis (DIE) which affects approximately 1% of women with endometriosis. BE commonly presents with lower urinary tract symptoms such as frequency, dysuria, hematuria, and, less frequently, bladder pain and urgency. The diagnosis and treatment of this condition could be difficult and requires multidisciplinary care. Due to overall rare cases, BE might pose a challenge, both to diagnose and treat. This article aims to share an experience in order to increase awareness and insight about BE for practising gynaecologist and urologist. Case: A Thirty-one years old woman, nulligravida, complained of painful, bloody stained urine, which occurs during menstruation since married for the last 18 months. Previously patient had a regular menstruation cycle with moderate pain and normal menstrual volume and no history nor any specific symptoms of disease. Gynaecological examination showed no remarkable finding. Ultrasound scan (US) by gynaecologist showed a mass protruded from the posterior wall of bladder. Cystoscopic finding by a urologist showed an adenomatous reddish nodular mass, and TUR was conducted. Pathological examination showed a cystitic glandulare. After three months temporary improvement, the symptoms reoccur. The patient underwent US and CT scan, again showed a mass, and another two rounds of TUR were conducted, to remove all residual mass. After three surgeries with no significant improvement, a team of gynaecologist and urologist were set to conduct a laparoscopic partial cystectomy with cystoscopy guidance to achieve complete excision of the lesion. The modified technique, which results in symptoms-free recovery, will be described in detail. Conclusion: BE could be challenging both in diagnostic and treatment. Cystoscopy and TUR are not recommended to diagnose and manage the lesions. A multidisciplinary approach is needed, and concomitant Laparoscopy with cystoscopy for partial cystectomy might give a satisfying outcome.Keywords: Bladder Endometriosis, Deep Infiltrating Endometriosis, Cystoscopy, Laparoscopic partial cystectomy, Lower urinary tract symptoms.